Management of maxillary first premolars with atypical anatomy, a new proposal for the approach of the cervical tooth region. Report of two cases and a literature review - Molina Quispe , Jairo Jhoel (2025)
Anatomical variations of the root canal system are rare, however premolars are the ones that present the most variability compared to other teeth. The aim of this study was to describe the endodontic management of three-rooted first and second maxillary premolars with three independent root canals. The approach was performed under magnification, the instrumentation was hybrid and the obturation was performed with a calcium silicate-based sealant. Several cases of this anatomical variation have been reported, therefore a literature review was also carried out to evaluate the presentation and clinical management. Clinicians should be aware of anatomical aberrations that could become evident during the preoperative and intraoperative treatment. Magnification and cone beam computed tomography will play an important role in the long-term prognosis of these cases.